If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2g + 7 = 3 Reorder the terms: 7 + -2g = 3 Solving 7 + -2g = 3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2g = 3 + -7 Combine like terms: 7 + -7 = 0 0 + -2g = 3 + -7 -2g = 3 + -7 Combine like terms: 3 + -7 = -4 -2g = -4 Divide each side by '-2'. g = 2 Simplifying g = 2
| 4x-x+3=x+15 | | 5x^3-2x^2-25x+10= | | 2x^2-11x-11=0 | | -3c-4=8 | | x^2+20x+47= | | -8(X-2)-5(3-X)+16=15-4(3-X) | | 4x-6-x=12 | | 7x+1=71 | | -2e-6=10 | | -7f=21 | | 5a+4=3a+2 | | 7y-2=7y-y | | 8x+4+130+3x-6=180 | | 36=4(9-5) | | 6x+6=-54 | | 3(2a+5)=5(3a-6) | | -4+5h=2+3h | | 10h+125=7h+230 | | 3k+-2=10 | | 7h+125=7h+230 | | .03x+.1(200-x)=.05(200) | | 3(b-5)=-2b | | 4(k-3)=-6(-2k+2) | | 7Z+10-4z=1+2z+7 | | .5(x+3)=2.5 | | 7x-9=68 | | y^2+9y+7=-7 | | =-0.4+9.5 | | 3a^2+16a+5=0 | | -(8x-5)-(2x-6)+4=-5(x-8)-(9x+7)+6 | | 2x^2+6x+9=5+16-8x | | -4y^2+32y-64= |